Clinical significance of the number of retrieved lymph nodes in early gastric cancer with submucosal invasion. Issue 46 (18th November 2022) - Kim, Dae Hoon; Yun, Hyo Yung; Ryu, Dong Hee; Han, Hye Sook; Han, Joung-Ho; Kim, Ki Bae; Choi, Hanlim; Lee, Taek-Gu
Abstract : The prognosis of early gastric cancer (EGC) with submucosal invasion is favorable; however, several cases of recurrence have been reported even after curative gastrectomy. This study aimed to investigate risk factors and evaluate the clinical significance of the number of retrieved lymph nodes (LNs) in EGC with submucosal invasion. We retrospectively analyzed the data of 443 patients with gastric cancer with submucosal invasion after curative gastrectomy for recurrent risk factors. Recurrence was observed in 22 of the 443 gastric cancer patients with submucosal invasion. In the univariate analysis, the risk factors for recurrence were the number of retrieved LNs ≤ 25 and node metastasis. In the multivariate analysis, retrieved LNs ≤ 25 (hazard ratio [HR] = 5.754, P -value = .001) and node metastasis (HR = 3.031, P -value = .029) were independent risk factors for recurrence after curative gastrectomy. Body mass index was related to retrieved LNs ≤ 25 in univariate and multivariate analyses (HR = .510, P  = .002). The number of retrieved LNs and node metastases were independent risk factors for EGC with submucosal invasion. For EGC with submucosal invasion, retrieved LNs > 25 are necessary for appropriate diagnosis and treatment.